Identification and Prioritizing Building Indices of Urban Planning in Urban Life Capability (Case Study: Four Regions of Kerman) - Ali Asghar Abdollahi; Morteza Hassanzadeh (جغرافیای اجتماعی شهری, 2017)
Ever-growing and accelerating urbanization in recent decades caused cities to confront challenges like reducing feelings and quality of Life, lack of sense of social belong, social- economic inequalities and expanding ecological problems. Therefore, the purpose of this study is to identify and determine the most influential indicator of urban planning in life capability of four regions of Kerman city. The research method is descriptive - analytical and in terms of purpose, it is an applied research. According to the research topic and the study area, the data collection method was using a questionnaire, in which 40 experts from the current status of the city were selected using the Delphi technique. Reliability of used data have been calculated as 0.842 utilizing the Cronbach's alpha. For data analysis, there is a sample t-test and a step-by-step regression model and for determining the share of each indicator investigated Quaternary areas of Kerman city, Arc GIS software was used. Obtained results from the T-test Show that experts' opinion about the urban planning building indices in neighborhoods of Kerman city; on the basis of considering the test value, which is number 3 here and is moderate. Also, the results of the regression model indicate that, among the investigated indicators, the investigated body mass index with a beta coefficient of 0.486 then the economic and environmental index or the beta coefficient of 0.341and, in the end, the social indicator with the beta coefficient of 0.278 % has the highest share in life capability in the city of Kerman.